C83 USE OF CANGRELOR IN A 63 YEARS OLD MEN SUFFERING FROM ACUTE INFERIOR ST–ELEVATION MYOCARDIAL INFARCTION AND SEVERE IDIOPATHIC THROMBOCYTOPENIC PURPURA: A CASE REPORT. (18th May 2022) - Cocozza, S; Formigli, D; Parente, A; Pirozzi, E; Franco, V; Moscato, F; Amico, V; Vallone, R; Scherillo, M
Abstract: A 63–year–old man suffering from systemic arterial hypertension, thalassemic trait, recent right ureteral stent implantation, dysthyroidism and thrombocytopenia presented to the Emergency Department with acute chest pain and ST elevation in inferior leads and 2nd degree atrioventricular block. He suffered from idiopathic thrombocytopenic purpura since February 2020, with baseline platelet level (PLT) <10, 000/mm³ requiring treatment with deltacortene 5 mg, tranexamic acid 1000 mg x 3/day and fostamatimib 100 mg x 2/day. Upon arrival in the Cardiology Intensive Care Unit (UTIC) an echocardiogram was performed and confirmed inferior myocardial infarction. First laboratory results were significant for PLT of 9, 000/mm³ and Troponin I peaked at 31, 838 pg/mL. The patient received Acetylsalicylic acid (ASA) 300 mg iv then was urgently transported to the Cath–Lab. Coronary angiography revealed mid right coronary artery occlusion, subsequently underwent primary percutaneous coronary intervention with multiple pre–dilations and placement of dual 3.5x28mm and 4.0x28mm TiNO bioactive metal stent with excellent angiographic results. A temporary Pacemaker was implanted. It was started Cangrelor bolus 30 µ/kg followed by infusion at 4 µ/kg/min for 6 hours associated with unfractionated sodium heparin at a reduced dosage of 50 IU/kg during the procedure and with a subsequent switch to Clopidogrel after an oral bolus of 300 mg. After 24 hours, the patient removed the temporary PMK for resolution of the AV block. The haematologist consultant advised to increase fosfatimib to 150 mg x 2/day and recommended the use of Human Immunoglobulin iv from the second day of hospitalization for 2 days. The patient was discharged on the seventh day, asymptomatic, with dual antiplatelet therapy (DAPT) with ASA 100 mg and Clopidogrel 75 mg daily and did not experience any bleeding during hospitalization. At a one–month follow–up, the patient is symptomatic and continued to tolerate ASA and Clopidogrel with stable PLT of 11, 000/mm³. In treating for STEMI, the treatment regimen consists of DAPT that increases risks for bleeding. In patients with thrombocytopenia, the risk for bleeding is multiplied and there are no clinical trials where patients with low platelet count are included, all therapeutic decisions must be made based on clinician's experience and experts' consensus. The use of Cangrelor proved to be safe and effective during STEMI even in patient with severe thrombocytopenia.